Insect immunorecognition - E Ottaviani (Invertebrate Survival Journal, 2005)
The mechanisms of the innate immunity in the insects have been reviewed. In particular, the cellular component (phagocytosis, encapsulation, melanization, nodule formation, wound healing, hemolymph clotting and transplantation) and the humoral component (lectins, cytokine-like molecules and anti-microbial peptides) of the hemolymph have been investigated.